The proceedings of the 16th Annual Conference of China Electrotechnical Society Volume III - He, Jinghan; Li, Yaohua; Yang, Qingxin; Liang, Xidong; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book gathers outstanding papers presented at the 16th Annual Conference of China Electrotechnical Society, organized by China Electrotechnical Society (CES), held in Beijing, China, from September 24 to 26, 2021. It covers topics such as electrical technology, power systems, electromagnetic emission technology, and electrical equipment. It introduces the innovative solutions that combine ideas from multiple disciplines. The book is very much helpful and useful for the researchers, engineers, practitioners, research students, and interested readers.
Keywords: Electrical engineering; Electronics; Electric power production; Electronic circuits; Electrical and Electronic Engineering; Electronics and Microelectronics, Instrumentation; Electrical Power Engineering; Electronic Circuits and Systems; Electrical engineering -- Congresses